The combined value of wind and solar power forecasting improvements and electricity storage. (15th March 2018) - Hodge, Bri-Mathias; Brancucci Martinez-Anido, Carlo; Wang, Qin; Chartan, Erol; Florita, Anthony; Kiviluoma, Juha
Highlights: The value of renewable energy forecasting is analyzed for high wind and solar scenarios. The value of energy storage is analyzed for high renewable energy scenarios. Each technology is evaluated both individually and in combination with the other. The integrated value remains relatively equal to the individual contributions. Renewable energy forecasting and energy storage neither compete nor collaborate for flexibility value. Abstract: As the penetration rates of variable renewable energy increase, the value of power systems operation flexibility technology options, such as renewable energy forecasting improvements and electricity storage, is also assumed to increase. In this work, we examine the value of these two technologies, when used independently and concurrently, for two real case studies that represent the generation mixes for the California and Midcontinent Independent System Operators (CAISO and MISO). Since both technologies provide additional system flexibility they reduce operational costs and renewable curtailment for both generation mixes under study. Interestingly, the relative impacts are quite similar when both technologies are used together. Though both flexibility options can solve some of the same issues that arise with high penetration levels of renewables, they do not seem to significantly increase or decrease the economic potential of the other technology.